An Assessment of Behavior Change Techniques in Two Versions of a Dietary Mobile Application: The Change4Life Food Scanner - Mahdi, Sundus; Michalik-Denny, Emily K.; Buckland, Nicola J. (Frontiers in Public Health, 2022)
The Change4Life Food Scanner app is a UK Government dietary app designed to provide feedback on the nutritional content of packaged foods to parents and their children. To understand its intended mechanism of behavior change and how Behavior Change Technique (BCT) content evolves with app updates, this research aimed to map out the BCTs of two versions of the Change4Life Food Scanner app. Two coders undertook a descriptive comparative analysis of the use of BCTs in the Food Scanner app using the Behavior Change Technique Taxonomy [both the outdated (v1.6) and updated (v2.0) versions of the app were coded]. Results showed that both versions encompass the BCTs “goal setting (behavior)”, “feedback on behavior”, “social support (unspecified)”, “instruction on how to perform behavior”, “salience of consequences”, “prompts/cues” and “credible source”. The outdated version contained the BCT “behavior substitution” which had been dropped in the updated version. The updated version featured the additional BCTs “information about social and environmental consequences”, “information about emotional consequences”, “social reward” and “social incentive” and was comparatively more BCT intensive in terms of content and occurrence. The BCT content of the Food Scanner app resembles that of existing dietary apps and incorporates several BCTs which have previously been found to be effective. Future work to evaluate the effectiveness of the app is recommended. This will provide insight into whether the combination of BCTs used in the Change4Life Food Scanner app are effective in improving dietary choices.